Programa de mejoramiento 1981-1986 - Beebe, Stephen E. (International Center for Tropical Agriculture, 1987)
A brief account of the bean breeding program for resistance to Thanatephorus cucumeris from 1981 to 1986 at CIAT and for Central America and the Caribbean is presented. Black and red bean parents used in the crossing programs are listed. While population selections have all been conducted under field conditions in Esparza, Costa Rica, inoculation tests under moist chamber conditions have been conducted at CIAT. The fact that resistance remains stable across environments for some sources, but not for the particular case of BAT 93 progeny, is discussed. (CIAT)